The Explosive world of volcanoes with Max Axiom, super scientist - Harbo, Christopher author; Smith, Tod. illustrator (London : Raintree, 2008)
Graphic science demonstrates and explains science. Whether shrinking down to the size of an ant or riding on a sound wave, it makes science a lot more accessible, by explaining science concepts and reinforcing scientific knowledge.